Aelfric and the cult of saints in late Anglo-Saxon England - Gretsch, Mechthild (Cambridge, UK ; New York : Cambridge University Press, 2005)
"In this study, Gretsch analyses Aelfric's Lives of five important saints in the light of their cults in Anglo-Saxon England, namely Gregory, the Roman pope; Benedict, the founder of western Monasticism; Cuthbert, the Northumbrian saint; Swithun of Winchester; and Aethelthryth of Ely. This analysis gives the reader glimpses of 'Aelfric at work': he adapts the cults and rewrites the received Latin hagiography of the five saints, with the result that each of their English Lives conveys a distinct message to the contemporary political elite and to a lay audience at large."--Jacket.
Aelfric's sanctorale and the Benedictional of Aethelwold -- Gregory : the apostle of the English -- Cuthbert : from Northumbrian saint to saint of all England -- Benedict : father of monks--and what else? -- Swithun and Aethelthryth : two saints 'of our days'.
Includes bibliographical references (pages 248-257) and indexes.
Print version record.
Keywords: Aelfric, -- Abbot of Eynsham; Aelfric, -- Abbot of Eynsham; Aelfric (Grammaticus).; Christian hagiography -- History -- To 1500.; Christian saints -- Cult -- England -- History -- To 1500.; Aelfric; RELIGION -- Christian Theology -- Angelology & Demonology; Christian hagiography; Christian saints -- Cult; England; Heiligenverering; Heiligenverehrung; England; To 1500; Electronic books; History